2022
DOI: 10.1186/s12935-022-02591-1
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanin 7 promotes osteosarcoma cell invasion and metastasis by inducing EMT and activating the FAK-Src-Ras-ERK1/2 signaling pathway

Abstract: Background Tetraspanins are members of the 4-transmembrane protein superfamily (TM4SF) that function by recruiting many cell surface receptors and signaling proteins into tetraspanin-enriched microdomains (TEMs) that play vital roles in the regulation of key cellular processes including adhesion, motility, and proliferation. Tetraspanin7 (Tspan7) is a member of this superfamily that plays documented roles in hippocampal neurogenesis, synaptic transmission, and malignant transformation in certai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Although TSPAN7 is an anti-tumor factor in bladder cancer, it promoted lung cancer progression by inhibits the expression of E-cadherin and vimentin, which raises the level of N-cadherin ( 48 ). It also has an interaction with the activation of β1 integrin-mediated downstream FAK-Src-Ras-ERK1/2 signaling pathway in osteosarcoma ( 49 ), boosting the cell epithelial-mesenchymal transition (EMT) process, indicating that the mechanisms of this gene and its downstream products still need to be explored. In lung cancer, AKR1B1 is a STAT3 activator that promotes glutathione de novo synthesis, eliminates ROS, protects cell from death, and reduces EGFR TKI drug sensitivity by upregulating the cystine transporter SLC7A11, it would be a therapeutic target for dealing with EGFR TKI resistance ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although TSPAN7 is an anti-tumor factor in bladder cancer, it promoted lung cancer progression by inhibits the expression of E-cadherin and vimentin, which raises the level of N-cadherin ( 48 ). It also has an interaction with the activation of β1 integrin-mediated downstream FAK-Src-Ras-ERK1/2 signaling pathway in osteosarcoma ( 49 ), boosting the cell epithelial-mesenchymal transition (EMT) process, indicating that the mechanisms of this gene and its downstream products still need to be explored. In lung cancer, AKR1B1 is a STAT3 activator that promotes glutathione de novo synthesis, eliminates ROS, protects cell from death, and reduces EGFR TKI drug sensitivity by upregulating the cystine transporter SLC7A11, it would be a therapeutic target for dealing with EGFR TKI resistance ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…TSPAN7 inhibits the expression of E-cadherin and vimentin, which raises the level of N-cadherin44. 44 It also has an interaction with the activation of β1 integrin-mediated downstream FAK-Src-Ras-ERK1/2 signaling pathway 45 , boosting the cell epithelial-mesenchymal transition (EMT) process. Interestingly, TSPAN7 also exerts an anti-tumor effects via the PTEN/PI3K/AKT pathway 46 , indicating that the mechanisms of this gene and its downstream products still need to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that tumor cells enhance the ability of tumor cell migration and movement by means of EMT and promote tumor invasion and metastasis [32]. More and more studies have shown that EMT is an important link in tumor invasion and metastasis [33,34] and promotes the invasion and migration ability of lung cells [35]. Its main characteristics are the increase of vimentin expression and the decrease of E-cadherin expression.…”
Section: Discussionmentioning
confidence: 99%